Complete lumbarization with calcified disc herniations at L5S1 and S1-2 levels treated with percutaneous endoscopic interlaminar discectomy: a case report and technique note - Lisheng, Hou; Feng, Ge; Dong, Zhang; Tianjun, Gao; Shaokui, Nan; Xuedong, Bai; Qing, He (Frontiers in Surgery, 2023)
Study Design. A retrospective case report. Objective. To report a case with complete lumbarization(Castellvi-IB) who developed symptomatic calcified disc herniations at L5S1 and lumbarized S1-2 levels achieved excellent neurological recovery following percutaneous endoscopic interlaminar discectomy（PEID). Summary of Background Data. In 1984, Castellvi et al classified Lumbosacral transitional vertebra (LSTV) into four types. The classification wrongly assumed type I LSTV anomalies as only type I sacralization, not realizing type I lumbarization also belonged to type I LSTV, while the latter exhibits well-developed S1-2 disc (lumbosacral transitional disc, LSTD). Patients with type I lumbarization rarely developed disc herniations concomitantly at L5S1 and LSTD levels, while extremely rare to develop calcified disc herniations at the two levels concomitantly. PEID has been developed to perform discectomy for neurologic decompression at the lumbar region, especially at the lowest level when higher iliac crest and/or widen transverse process exists. Methods. A 47-year-old male came to our hospital complaining of intractable left leg radiating pain for 3 weeks after chronic radiating pain for 4 years. Physical examination found hyperalgesia at lateral side of left calf, decreased dorsal flexion strength of ankle (grade 4/5), and positive sign of straight leg raising test at left side (30°). The preoperational Lambar JOA (Japanese Orthopaedic Association) score was 12. Image examinations including whole spinal radiograph, magnetic MR and CT confirmed complete lumbarization (Castellvi-IB) with calcified disc herniations at L5S1 and LSTD levels at left side. PEID was carried out at two index levels to realize decompression via left approach. Results. The patient’s neurological function recovered quickly. One day postoperatively, he began to walk without discomfort. Three months later his muscle strength recovered to normal. Six months later, the residual dysesthesia at posterolateral calf disappeared. The follow-up Lambar JOA score was 26. Conclusion. calcified LDH could develop at distal two levels concomitantly in type I complete lumbarization case. This anomaly might be misinterpreted as normal lumbar sequence by only lumbar MRI. PEID may be an effective procedure to treat such calcified disc herniations at one single time.